Willingness to pay per quality-adjusted life year of Non-Hodgkin Lymphoma patients in Vietnam - Y, Nguyen Tran Nhu; Huy, Phan Gia; Dung, Pham Xuan; Thap, Dang The (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
Objectives: To estimate Willingness to pay per quality-adjusted life year (WTP/QALY) of patients with Non-Hodgkin Lymphoma (NHL) and analyze related factors to WTP/QALY of NHL patients. Patients and methods: Cross-sectional study has been conducted based on surveying NHL patients, satisfying inclusion and exclusion criteria in 5 specialized hospitals of Vietnam from March to August 2018. The structured questionnaire on socio-demographic and clinical characteristics, EQ-5D-5L and WTP were built to directly interview patients. Regression and correlation analysis have been conducted to estimate the related factors to WTP/QALY. The data were analyzed with relevant statistical tests and simple linear regression using SPSS 20.0 statistical software provided by International Business Machines (IBM) - New York, United State of America. A p-value <0.05 was considered statistically significant. Results: Sample included 516 NHL patients with the ratio of men: women of 1.37:1, the average age of 53.57 ± 14.37 years old, the average time of NHL onset of 1.32 ± 0.63 years. The median value of WTP/QALY was accounted for 45,604,698.96 (0.00 – 187,311,321.74) VND/QALY. With the confidence interval of 95%, the statistically significant differences in LogWTP/QALY have been found between men and women (0.179; 95% CI: 0.023 – 0.335; p = 0.025); fulltime- working patients and non-working patients (0.270; 95% CI: 0.275 – 0.512; p = 0.022), intellectual workers and unemployed/ housewife/ disability patients (0.555; 95% CI: 0.095 – 1.014; p = 0.009); lost-income and unlost-income status (0.267; 95% CI: 0.090 – 0.445; p = 0.003), family income (r = 0.272, p = 0.000) and patient income (r = 0.288, p = 0.000), HR-QoL (r = 0.436; p = 0.000). Linear regression analysis with 95% reliability showed R2= 0.291; p = 0.000 with two related factors to LogWTP/QALY including HR-QoL coefficient (β = 1.339; p = 0.000) and family income (β = 8.50 x 10-9; p = 0.014). Conclusion: The median value of WTP/QALY was accounted for 45,604,698.96 (0.00 – 187,311,321.74) VND/QALY. With the confidence interval of 95%, linear regression analysis showed two related factors to LogWTP/QALY including HR-QoL coefficient and family income.